A systematic review of the incidence and prevalence of comorbidity in multiple sclerosis: Overview - Marrie, Ruth Ann; Cohen, Jeffrey; Stuve, Olaf; Trojano, Maria; Sørensen, Per Soelberg; Reingold, Stephen; Cutter, Gary; Reider, Nadia (Multiple sclerosis, 2015)
Background: Comorbidity is an area of increasing interest in multiple sclerosis (MS). Objective: The objective of this review is to estimate the incidence and prevalence of comorbidity in people with MS and assess the quality of included studies. Methods: We searched the PubMed, SCOPUS, EMBASE and Web of Knowledge databases, conference proceedings, and reference lists of retrieved articles. Two reviewers independently screened abstracts. One reviewer abstracted data using a standardized form and the abstraction was verified by a second reviewer. We assessed study quality using a standardized approach. We quantitatively assessed population-based studies using the I2 statistic, and conducted random-effects meta-analyses. Results: We included 249 articles. Study designs were variable with respect to source populations, case definitions, methods of ascertainment and approaches to reporting findings. Prevalence was reported more frequently than incidence; estimates for prevalence and incidence varied substantially for all conditions. Heterogeneity was high. Conclusion: This review highlights substantial gaps in the epidemiological knowledge of comorbidity in MS worldwide. Little is known about comorbidity in Central or South America, Asia or Africa. Findings in North America and Europe are inconsistent. Future studies should report age-, sex- and ethnicity-specific estimates of incidence and prevalence, and standardize findings to a common population.